A Review of Medication Non-adherence in Chronic Diseases: Thin Line between Health, Harm and the Vital Role of Pharmacists - Ojo, Phillips Damilare; Anizor, Glory Vincent; Uwamusi, Mighty; Sulaiman, Hikmat Opeyemi; Shonibare, Khadijat Boluwatife; Ojo, Clement Oluwagbemiga; Otaru, Oyiza Latifat (The Nigerian Journal of Pharmacy, 2025)
Adherence to prescribed medication regimens is essential for the effective management of chronic conditions. Non-adherence to treatment plans undermine therapeutic effectiveness, increases healthcare costs and elevates the risk of complications. Non-adherence, however, is complex and often results from numerous interacting factors. Some of these factors may be related or unrelated to the individual. Adherence to medications comprises three interrelated stages: initiation, implementation and discontinuation. Patients who fail to initiate treatment and those who discontinue treatment prematurely often experience the worst clinical outcomes. Numerous studies on non-adherence have proposed models that help explain why patients fail to adhere to their medications. While there is a paucity of studies on the reasons patients prematurely stop taking their medications, existing research suggests that the decision is often based on a combination of social, environmental and personal factors including adverse drug reactions. In the management of chronic diseases, there is often a delicate balance between effective disease control and clinical deterioration, underscoring the thin line between health and harm. It is therefore important for healthcare professionals, researchers, and stakeholders to prioritize efforts aimed at promoting adherence in individuals who suffer from chronic diseases. Pharmacists, as accessible members of the healthcare team, have a significant role to play. Some of their responsibilities include effective patient education and counselling, medication therapy management, monitoring and followup, use of medication management tools, collaboration with other healthcare providers, telepharmacy, integration of digital health technologies and tools, simplifying treatment regimens and community outreach and advocacy. To effectively manage chronic conditions, medication adherence must be prioritized. Patients should be adequately educated on the significance of following their treatment regimen and the potential consequences of non-adherence. Individualized strategies that address patients’ unique beliefs and barriers to adherence should also be adopted.